Curriculum Development at PT. KAI Training Center Ir. H. Djuanda Bandung - Saputra, Yori Andes; Hernawan, Asep Herry (Westscience Press, 2024)
Investing in Human Resources (HR) is crucial for a company's success despite technological advancements. High-quality human resources are essential, serving as the driving force within an organization. The Manager Curriculum collaborates to design a competency-based curriculum tailored to the company's needs, emphasizing attitude, skills, and knowledge. The syllabus outlines long-term learning plans. Learning methods include discussions, case studies, and exercises to engage participants effectively. Teaching materials, in the form of handouts, are prepared and approved to facilitate systematic learning. Overall, nurturing human resources is vital for an organization's growth and competitiveness.